Implementasi model pembelajaran inovatif team games tournament untuk meningkatkan minat belajar Siswa MTsN 8 Blitar - Safitri, Via Dwi Ria Dwi Ria (Maliki Interdisciplinary Journal, 2025)
This study aims to improve students’ interest in learning Social Sciences (IPS) through the implementation of the innovative Team Games Tournament (TGT) learning model. The background of this study is the low participation and learning motivation of class VII I MTsN 8 Blitar students as indicated by inactivity in discussions, lack of response to teacher questions, and low learning outcomes. This study is a Classroom Action Research (CAR) carried out in two cycles. Each cycle consists of the planning stage, action implementation, observation, and reflection. Data were collected through observation of student activities, learning outcome tests, and interviews with teachers. The results of the study showed an increase in students’ interest in learning and learning outcomes after the implementation of the TGT model. In the pre-cycle stage, only 13 students (34.2%) achieved a score of ≥ KKM. After cycle I, the number of students achieving KKM increased to 21 students (55.2%). A more significant increase occurred in cycle II, where 32 students (84.2%) achieved KKM. In addition to quantitative improvements, students also showed active involvement in learning, both cognitively, affectively, and psychomotorically. Learning became more enjoyable, interactive, and competitive. These results prove that the TGT model is effective in increasing students’ interest in learning and is worthy of being applied as an alternative learning strategy, especially in social studies learning.